Determination of iron content in Malaysian coloured rice - 503280 Ng, Pek Ngah,ld1987-; Rahmalan Ahmad, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010